Tigecycline-Amikacin Combination Effectively Suppresses the Selection of Resistance in Clinical Isolates of KPC-Producing Klebsiella pneumoniae - Ni, Wentao; Wei, Chuanqi; Zhou, Chufei; Zhao, Jin; Liang, Beibei; Cui, Junchang; Wang, Rui; Liu, Youning (Frontiers in Microbiology, 2016)
By far, only tigecycline, colistin and some aminoglycosides still show favorable in vitro activities against carbapenem-resistant Enterobacteriaceae. However, rapid emergence of resistance often occurs during long-term treatment in clinic, challenging these last resort antimicrobials. In this study, we measured mutant prevention concentration (MPC) and mutant selection window (MSW) of tigecycline, colistin and amikacin alone and in combination for clinical isolates of KPC-producing K. pneumoniae, and characterized the resistant mutants recovered. The MPC90 of 30 tested isolates for tigecycline, colistin and amikacin were 16, >128 and 128 mg/L, respectively. The average MSW of tigecycine-amikacin, tigecycline-colisitn, and amikacin-colistin combinations for 4 representative strains were 11.99, 200.13 and 372.38, respectively. A strong correlation was found between the MSWcombination and the product of MSW of each single drug. Combinations of 1MIC multiple tigecycline and 1MIC multiple amikacin could result in 1000-10000 fold reduction in mutational frequency relative to their individual mutational frequencies, and combinations of 1 MIC multiple amikacin and 1.5-2 MIC multiple tigecycline could successfully restrict the recovery of resistant mutants on agar plates. However, 2 MIC multiple colistin in combination with 2 MIC multiple tigecycline or amikacin merely resulted in approximately 10 fold decrease in the mutational frequency. In conclusion, this study showed tigecycline-amikacin combination could effectively suppress the selection of resistance at low concentrations compared with the colistin-tigecycline and colistin-amikacin combinations, suggesting that this combination may be useful in clinical therapy.